Mathematical Literacy Skills in Rational Number Material Class VII Reviewed from Learning Motivation - Kusniawati, Nia; Yuliawati, Lia; Yusuf, Yusfita (Mathematics Education Study Program, 2025)
This study examines the mathematical literacy skills of seventh-grade students at State Junior High School (SMP) 1 Tanjungsari and their relationship with learning motivation. The objective of this research is to analyze the impact of students' learning motivation on their mathematical literacy abilities. This study employs a descriptive qualitative method, involving 34 students from class VII-H in the first semester of the 2024/2025 academic year. Data collection methods include a three-item descriptive test, a learning motivation questionnaire, and interviews with selected students. The results indicate that the average mathematical literacy score was 29.26 (out of 100), with 1.02% of students categorized as having high literacy, 1.70% as medium, and 79.41% as low. Learning motivation levels were classified as high (17.65%), medium (61.76%), and low (20.58%). In conclusion, students with high motivation and literacy demonstrated proficiency in all mathematical literacy indicators, whereas students with low motivation exhibited weaker literacy skills and failed to meet all indicators. Notably, even students with moderate motivation displayed low literacy skills and did not achieve all expected indicators.